ภาวะหมดไฟในการทำงานและปัจจัยที่เกี่ยวข้องของนักเทคนิคการแพทย์ ในจังหวัดกรุงเทพมหานคร - วราภรณ์ เลิศวิลัย (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Objective: To explore the Burnout and associated factors of Medical Technologist in Bangkok. Methods: A cross-sectional descriptive study was performed is 195 Medical technologist in Bangkok. The questionnaires were composed of: 1) Personal information; 2) Occupational stress indicator questionnaire; 3) Maslach Burnout Inventory (MBI) questionnaire in Thai version was interpreted by Suwanwathin P. The association between Demographic data occupational stress factors and burnout syndrome who were analyzed by chi-square test. The logistic regression was used to identify the predictors of Medical technologist’burnout Results: There were 195 medical technologists in Bangkok participated in this study. Among them, 21% were diagnosed as burnout syndrome. By using Chi-square, the results showed that average income, government position, and overtime office hour were significantly associated with burnout syndrome (p<0.05). Workload, interpersonal, and company administration had an impact on occupational stress. These three factors, therefore, were significantly associated with burnout syndrome as well (p<0.05). Conclusion: Medical technologists were diagnosed as burnout syndrome; 21%. the characteristics factors; average income and overtime office hour also, the factors indicated occupational stress; job responsibilities and interpersonal relationship were significantly associated with burnout syndrome